PERBANDINGAN GAMBARAN DARAH ULAR SANCA BATIK (Malayophyton reticulatus) LOKAL JAWA DAN KALIMANTAN - Slamet Raharjo; Sri Hartati; Sedarmanto Indarjulianto; Rini Widayanti (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Reticulated python (M. reticulatus) Java and Kalimantan locality highly demand as pet animal. Blood profile has an important role on animal health status. This research was aim to study the blood profile comparison of Java and Kalimantan M. reticulatus. Ten blood samples of Java M. reticulatus and 10 samples of Kalimantan M. reticulatus were used in this study. As much as 1 ml blood sample was collected from ventral coccygeal vein of adult healthy M. reticulatus. Blood sample put into tube with EDTA then analized at Internal Department Laboratory, Faculty of Veterinary Medicine UGM. Based on blood samples analize results, adult healthy Java M. reticulatus shows the higher value on parameters of erytrocyte, leucocyte, PCV, MCH, heterophyl, limphocyte and monocyte, while haemoglobin, TPP, MCV, MCHC, azurofil and monosit were lower than Kalimantan M. reticulatus. There were no significant differences (P>0,05) between blood profile of Java and Kalimantan M. reticulatus. It could be concluded that blood profile of Java and Kalimantan M. reticulatus is not different.